2019
DOI: 10.1155/2019/1354362
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Thirty-One Assessment Tests to Evaluate Mobility in Older Adults

Abstract: Assessments of gait, balance, and transfer in elderly people play a valuable role in maintaining healthy aging and preventing a decline in mobility. Several evaluation tools have been proposed; however, clinicians should select the most accurate ones wisely, based on numerous criteria. This systematic review aims to identify all applicable elderly mobility assessment tests and show their measurement properties with as much detail as possible. Initially, a broad search was performed. Articles were screened base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 80 publications
2
71
1
Order By: Relevance
“…These can be even more demanding than gait in terms of cognitive resources required for planning, orientation in space and organization purposes [15]. The ability to perform such activities, which are commonly classified under the umbrella of "functional mobility", can be easily assessed using a wide range of tools [16]. Among them, the Timed-Up-and-Go test (TUG, [17]) is one of the most common, owing to its clinical utility in diagnosing risk of falls [18,19] in community-dwelling and frail older adults.…”
Section: Introductionmentioning
confidence: 99%
“…These can be even more demanding than gait in terms of cognitive resources required for planning, orientation in space and organization purposes [15]. The ability to perform such activities, which are commonly classified under the umbrella of "functional mobility", can be easily assessed using a wide range of tools [16]. Among them, the Timed-Up-and-Go test (TUG, [17]) is one of the most common, owing to its clinical utility in diagnosing risk of falls [18,19] in community-dwelling and frail older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of physical tests has not kept up with the global population increase of older adults. There is a lack of normative values in outcome measures for older adults living in RAC as most work to date has been on healthy older adults living in the community [54]. An example of this is of the outcome measures used in this study only three have had a minimal detectable change identified: MoCA 4 points [36]; Brief BESTest 4 points [55]; SPPB total 1 point [56]; however, only the Brief BESTest established this for a population of older adults living in RAC.…”
Section: Objective 2 To Test the Appropriateness Of Data Collection mentioning
confidence: 99%
“…Specifically, the Timed Up and Go and the Six-Minute Walk Test are two commonly used measures particularly in older hospitalized patients. However, previous studies showed that these measures have ceiling effects in older hospitalized patients, which severely limit their ability to measure older patients' mobility function [12]. Thus, the commonly used measures cannot validly assess older patients' mobility.…”
Section: Introductionmentioning
confidence: 99%